Penentuan Upah Nelayan di Kelurahan Pancuran Bambu - Tanjung, Budiansyah; Nasution, Muhammad Arsad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
Wage is money that is paid in return for services or competasion for losses received by the workes for the outpouring of their labor to other people who have the status of toke (employer). As for the problem in this study, the part of determining the wages of fishermen in the Pancuran Bambo Village Sibolga District Sambas Sibolga City in the perspective of Muamalah Fiq, this type of research is a qualitative field research that is sourced from fact finding from the field in addition using interview methods and observation methods and also looking for facts from legal materials. This study aims to abtain accurate data on how to determine the wages of fishermen in the Pancuran Bamboo Village Sibolga District Sambas City Sibolga City competasion of losse receavid by the workes this type of reseach is qualitative. The results of this study explain that the determination of fishermen’s wages in the Pancuran Bamboo Village Sibolga Sambas District Sibolga City is not in accordance with Islamic rules, which in the Qur’an and hadith giving wages to workers must be given as soon as possible and do not delay the wages of workers, the wages of fishermen in the Pancur Bambo Village Sibolga, this study to works this type of research is given as soon possible and do not deley the wages of workers.